2014
DOI: 10.1159/000357180
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus Serotype-2 Impairs Proliferation of Healthy Donors' T Lymphocytes

Abstract: Objectives: T lymphocytes are not infected by dengue virus (DENV), nevertheless it is possible that exposure to DENV may affect their function. T lymphocytes from DENV-infected individuals are impaired in their proliferative capacity, although this effect has been attributed to altered function of antigen-presenting cells rather than to an intrinsic defect on T lymphocytes. Here we analyzed whether T lymphocytes from healthy donors became impaired in their proliferative capacity following in vitro exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…In 2001, our group described a reduced frequency of CD4 + and CD8 + T lymphocytes and a poor ability for T‐lymphocyte proliferation in response to mitogens and dengue antigens in acute DENV‐infected patients, but re‐established in convalescence phase . Another study found that in vitro exposure to DENV‐2 of T lymphocytes isolated from healthy donors reduces the lymphoproliferative capacity in response to mitogen, suggesting that DENV‐2 can inhibit T cell‐mediated immunity, bypassing monocytes and dendritic cells, classical DENV cell targets .…”
Section: Discussionmentioning
confidence: 99%
“…In 2001, our group described a reduced frequency of CD4 + and CD8 + T lymphocytes and a poor ability for T‐lymphocyte proliferation in response to mitogens and dengue antigens in acute DENV‐infected patients, but re‐established in convalescence phase . Another study found that in vitro exposure to DENV‐2 of T lymphocytes isolated from healthy donors reduces the lymphoproliferative capacity in response to mitogen, suggesting that DENV‐2 can inhibit T cell‐mediated immunity, bypassing monocytes and dendritic cells, classical DENV cell targets .…”
Section: Discussionmentioning
confidence: 99%
“…T lymphocytes are not infected by dengue virus, nevertheless it is possible that exposure to virus and/or proteins viral may affect their function. T lymphocytes from DENV-infected individuals are impaired in their proliferative capacity, although this effect has been attributed to altered function of antigen-presenting cells rather than to an intrinsic defect on T lymphocytes [33]. The host immune responses have been considered as the major factor responsible for dengue pathogenesis, resulting in an altered immune response, which triggers T cell activation, and the release of cytokines and chemical mediators has been a risk factor in secondary Infection.…”
Section: Discussionmentioning
confidence: 99%